PSYCHOLOGICAL ASPECTS OF GAME ACTIVITY THAT ORGANIZES THE EDUCATIONAL BRAIN ACTIVITY - Gaziyeva Nigora Shamsuddinovna (Web of Journals Publishing, 2023)
The article describes the psychological features of kindergarten-age children's play, and shows that kindergarten-age children strive to reflect all aspects of life and act independently in their home activities.
Keywords: kindergarten, preschool age, game, psychology, activity, physical development, independent movement.